Metode Alternatif Penentuan Tingkat Hasil dan Harga Kompetitif: Kasus Kedelai - Masdjidin Siregar (Forum penelitian Agro Ekonomi, 1999)
EnglishA particular food crop may be deemed competitive if the crop provides farmers with a level of net returns that at least equals to the net returns from competing food crops. Competitive net returns can be reached by increasing yield level or by increasing output price level. Yield and output price levels that result in competitive net returns may be called respectively competitive yield and competitive output price. The computation of competitive yield and competitive output price is useful to see the competitiveness or the possibility of area changes of a particular crop under study. The computational methods have been initiated by Manwan et al (1990). However, the computational method regarding competitive yields suffers from shortcoming since it does not consider that, given unchanged technology and prices, an increase in yields requires an increase in costs. In order to reduce the weakness, this paper offers an alternative method. The alternative method is based on the assumption that, if the net return of a particular crop increases from (NRk0) to (NRj0), then the total variable cost should be multiplied by (NRk0/(NRj0)). Although the assumption has no convincing theoretical basis, the method is obviously better than the previous one. The application of the new method indicates that soybean can compete with corn even if soybean yield decreases by 30 percent. It should be noted that the data used in the analysis are from provincial level of Java. To have better results, one should apply similar analysis using data from district level or sub-district level by agro-ecological zones. IndonesianSuatu tanaman pangan dikatakan dapat bersaing dengan tanaman pangan lainnya kalau tanaman tersebut dapat memberikan tingkat penerimaan bersih paling sedikit sama dengan tingkat penerimaan bersih dari tanaman pangan pesaing. Jika tingkat penerimaan dari tanaman kedelai lebih rendah dari tingkat penerimaan dari tanaman jagung misalnya, maka daya saing kedelai dapat ditingkatkan dengan peningkatan hasil kedelai atau peningkatan harga kedelai. Salahsatu metode penghitungan tingkat hasil atau harga kompetitif digunakan oleh Manwan dkk (1990). Tetapi metode penghitungan tingkat hasil kompetitif tersebut mengandung kelemahan karena metode tersebut tidak mempertimbangkan bahwa, kalau teknologi dan harga-harga tidak berubah, peningkatan hasil memerlukan peningkatan biaya. Untuk mengatasi kelemahan itu, makalah ini menawarkan metode alternatif yang didasarkan pada asumsi bahwa peningkatan penerimaan bersih dari (NRk0) ke (NRj1) memerlukan biaya peubah total sebesar (NRk1/(NRj0) kali lipat. Hasil penggunaan metode alternatif ini terhadap Data Struktur Ongkos BPS menunjukkan bahwa kedelai dapat bersaing dengan tanaman jagung meskipun hasil kedelai turun 30 persen. Perlu dicatat bahwa data BPS tersebut merupakan data rataan tingkat provinsi. Untuk mendapatkan hasil yang lebih baik, metode tersebut sebaiknya digunakan pada data tingkat kabupaten atau kecamatan menurut keadaan agroekosistem.